Celestial Flames: Rabi'ah Al-Adawiyah's Spiritual Journey Through Love - IT, Suraiya (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
By referring to God as the Beloved, Rabi'ah al-Adawiah, the first Sufi woman, articulated the relationship with the Divine in a way that has come to be recognized as uniquely Sufi. The love described in the Pattern of Rabi'ah is thought to be pure love for God; the lover must walk along the route of love in order to remember God alone, not Hell or Paradise. When Rabi'ah speaks of "love," he means something more fundamental than something constrained by reward or hope. Her affection is truly lovely. The first woman to discuss the practicalities of Sufism in an approachable and comprehensible manner was Rabi'ah. The genuine embodiment of the relationship between a human being and God is found in Rabi'ah's love. She has contributed significantly to the growth of Sufism. I will explore Rabi'ah al-Adawiah's practice of love in this article. She was a follower of the Sufi Way, a mystical path within Islam. She will share stories of her efforts to witness truth in many realms, as well as her dreams and visions, as well as her sacred songs and poetry